2016
DOI: 10.1016/j.bbrc.2016.08.122
|View full text |Cite
|
Sign up to set email alerts
|

Desmin phosphorylation by Cdk1 is required for efficient separation of desmin intermediate filaments in mitosis and detected in murine embryonic/newborn muscle and human rhabdomyosarcoma tissues

Abstract: Desmin is a type III intermediate filament (IF) component protein expressed specifically in muscular cells. Desmin is phosphorylated by Aurora-B and Rho-kinase specifically at the cleavage furrow from anaphase to telophase. The disturbance of this phosphorylation results in the formation of unusual long bridge-like IF structures (IF-bridge) between two post-mitotic (daughter) cells. Here, we report that desmin also serves as an excellent substrate for the other type of mitotic kinase, Cdk1. Desmin phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…6b). Cyclin-dependent kinase-1 (Cdk-1) is responsible for this phosphorylation [43]: consistently, it was more active in Drp/MC muscle at P7 (Fig. 6c).…”
Section: Drp1 Can Affect Desmin Assembling Promoting Mitochondrial Rementioning
confidence: 86%
“…6b). Cyclin-dependent kinase-1 (Cdk-1) is responsible for this phosphorylation [43]: consistently, it was more active in Drp/MC muscle at P7 (Fig. 6c).…”
Section: Drp1 Can Affect Desmin Assembling Promoting Mitochondrial Rementioning
confidence: 86%
“…Most of PTMs cause disassembly of desmin network, with the exception of ubiquitination which leads to its degradation. Among other enzymes (PKA, PKC, PAK, CaMKII) (Winter et al 2014), desmin is phosphorylated by Rho kinase (Inada et al 1998), Aurora-B (Kawajiri et al 2003), and by Cdk1 (Makihara et al 2016), all PTMs required for efficient separation of desmin-IFs in mitosis (Inada et al 1999;Kawajiri et al 2003).…”
Section: Desmin and Posttranslational Modificationsmentioning
confidence: 99%
“… 47 , 48 , 49 The kinase activity of CDK1 plays a regulatory role in various types of tumors, including bladder cancer, 50 prostate cancer, 51 gastric cancer, 52 breast cancer, 53 colorectal cancer, 54 and rhabdomyosarcoma. 55 Generally, the kinases catalyze the phosphorylation of substrates. In contrast, our study showed that CDK1 regulated BMAL1 S42 dephosphorylation, leading to tumor progression.…”
Section: Discussionmentioning
confidence: 99%